Analysis of Sharia Economic Law on the Transformation of Non-Halal Fund Management in Islamic Financial Institutions in DSN Fatwa - Ariswanto, Dery; Nashrullah, M. Faiz; Sabilaturrizqi, Mashudah (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
Islamic financial institutions have unique characteristics that base all operations on Sharia principles, including the management of sources and uses of funds. However, in its operational practice, Islamic financial institutions are sometimes faced with the potential for receiving funds from non-halal sources. Responding to this issue, DSN-MUI issued Fatwa Number 123/DSN-MUI/XI/2018, which provides comprehensive guidance regarding the management of funds originating from the non-halal sector. The purpose of this study is to describe how to analyze the management of non-halal funds after the issuance of fatwa by the National Sharia Council of MUI No. 123/DSN-MUI/XI/2018. This research adopts a descriptive-analytical qualitative method to explore the transformation of non-halal fund management in Islamic financial institutions, which is then analyzed through the perspective of Islamic economic law to understand the implications of the practices that occur. This study concludes that the transformation of the management of non-halal funds in Islamic financial institutions after the issuance of DSN fatwa No. 123/DSN-MUI/XI/2018 shows an effort to adapt and implement the principles of Islamic economic law in separating and distributing these funds. Nevertheless, uniform implementation and a comprehensive understanding of the concept of TBDSP Funds still require strengthening in various Islamic financial institutions. Non-halal funds are funds obtained from sources that are contrary to Islamic religious principles. Non-halal funds actually cannot be recognized as an institution's income because non-halal funds come from haram and shubhat funds. Therefore, its management and distribution must be fully directed for the benefit of the ummah or social welfare. [Lembaga keuangan syariah memiliki karakteristik unik yang mendasarkan seluruh kegiatan operasionalnya pada prinsip-prinsip syariah, termasuk dalam pengelolaan sumber dan penggunaan dana. Namun, dalam praktik operasionalnya, lembaga keuangan syariah terkadang dihadapkan pada potensi penerimaan dana dari sumber yang tidak halal. Merespon hal tersebut, DSN-MUI mengeluarkan Fatwa Nomor 123/DSN-MUI/XI/2018 yang memberikan panduan komprehensif mengenai pengelolaan dana yang berasal dari sektor non halal. Tujuan dari penelitian ini adalah untuk mendeskripsikan bagaimana analisis pengelolaan dana non halal pasca dikeluarkannya fatwa Dewan Syariah Nasional MUI No. 123/DSN-MUI/XI/2018. Penelitian ini menggunakan metode kualitatif deskriptif-analitis untuk mengeksplorasi transformasi pengelolaan dana non-halal di lembaga keuangan syariah, yang kemudian dianalisis melalui perspektif hukum ekonomi Islam untuk memahami implikasi dari praktik yang terjadi. Penelitian ini menyimpulkan bahwa transformasi pengelolaan dana non-halal di lembaga keuangan syariah pasca dikeluarkannya fatwa DSN No. 123/DSN-MUI/XI/2018 menunjukkan adanya upaya adaptasi dan implementasi prinsip-prinsip hukum ekonomi syariah dalam memisahkan dan mendistribusikan dana tersebut. Namun demikian, penerapan yang seragam dan pemahaman yang komprehensif mengenai konsep dana TBDSP masih memerlukan penguatan di berbagai lembaga keuangan syariah. Dana non halal adalah dana yang diperoleh dari sumber yang bertentangan dengan prinsip-prinsip agama Islam. Dana non halal sebenarnya tidak dapat diakui sebagai pendapatan lembaga karena dana non halal berasal dari dana yang haram dan syubhat. Oleh karena itu, pengelolaan dan penyalurannya harus sepenuhnya diarahkan untuk kemaslahatan umat atau kesejahteraan sosial.]